PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI (Studi pada BADAN PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK, DAN KELUARGA BERENCANA) (Students' Journal of Economic and Management, 2015)
This study aimstoanalyzethe influenceof thecompensation and working conditionsof theemployees' workmotivation. Object ofstudyinthis paper IsBP3AKBCentralJava Province. The populationin this study wereall employeesBP3AKBCentralJava Province. Sampling techniqueused in this studyis themethod of'census sampling' 'the number of 65respondentsin the sample. Methods of data collectionusingquestionnaires(questionnaire) by distributinga list ofquestionstorespondto theinformation. The collected datawere analyzedusing atestinstrumentthat isused to testthe validity ofusing '' loading factor(KMO) 'and reliability testing usingCronbachalpha. Regression analysis, to testthe influence ofeachpartial- eachindependent variableswere testedwith thecoefficient of determination(R2), F-testandt-testmodelsto testandprove thepartial effectof each –eachfree variable. The results of theresearchare: (1) Compentation ipositive and significant impactonemployeework motivation. (2) Work Environmentandsignificant positive effectonemployeework motivation. Keywords: Compensation, Work environment, Work Motivation